Développer la réflexivité critique en cartographiant une controverse ? - Benoît Urgelli; Clémence Godin (Université de Provence, 2022)
Since 2017, a training program in mapping controversies has been offered to Master degree students in Education. The challenge is to develop the critical reflexivity of young apprentice-researchers, by inviting them to investigate a freely chosen mediatic, controversial and educational issue. They produce a cosmogram illustrating the complexity of the games of actors and arguments, being attentive to the possible influence of the arenas of media. At the end of this production, the students express a critical and reflective position about the studied controversy, and they explain, according to them, the learning aroused by this training. In this article, we analyze the different forms of reflexivity identifiable in the writings of students, linked to their investigative mapping controversy experiences. We discuss the hypothesis that mapping controversies on education, through the analysis of the complexity of the interplay of actors and mediated arguments, would promote the development of critical and reflective judgment.